BUILDING SYSTEM OF PERSONNEL MOVEMENT USING GLOBAL POSITIONING SYSTEM (GPS) DESIGN - Anwar Saryanto; Aries Boedi Setiawan; Suherman Suherman; Yusuf Novrianto (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Supervision process is an important phase performed by a leader in implementing activities so that the activities can run accordingly to the plan. The implementation of task done by Military personnel need supervision continuously by a leader. The development of advanced technology of electronics and communications in equipment and weapons and implementing navigation system using satellites. By designing a supervisory system to monitor personnel movements using Global Positioning System (GPS) will facilitate leaders to supervise personnel. GPS as a data receiver from satellites in the form of latitude, longitude of position coordinates. Wavecom modem as a data receiver from GPS Module. Delphi 7 Program will process data, then will display Google Maps showing position of the personnel, coordinates, and time of place movement done by the personnel. The network of GSM is needed as a data sender media. Coordinate data displayed in Google Maps in real time corresponds to the personnel position coordinate in reality.